Obtaining Competencies with Self-Determination Theory: The Music Therapy Internship. Issue 2 (19th August 2016) - Rushing, Jessica; Capilouto, Gilson J
Abstract: The purpose of this paper is to provide a conceptual framework that creates an environment of optimal learning for music therapy interns by supporting the psychological needs that facilitate intrinsic motivation, learning, and well-being. To accomplish this, supervisors will use self-determination theory (SDT) as a lens to view the training experience. The linear model presented matches (a) time, (b) emotional needs, (c) SDT psychological needs, (d) music therapy professional competencies, and (e) transitional roles. Employing the proposed model will permit supervisors to be proactive in addressing intern areas of need and growth. What follows is a review of literature on music therapy internship and SDT, rational for model development, and strategies for practice implementation.